Evaluation of basalt-based mortars incorporating local bio-fibers using the TOPSIS method: a technical, environmental, and economic assessment - Anak Agung Ngurah Dwipayana Putra; Putu Cinthya Pratiwi Kardita; I Made Agus Ariawan; Ni Ketut Ary Tubuh Harum Ningsih; William Steven Brian Syah (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
The construction sector in Bali still generates significant environmental waste, including from the tabas stone craft industry, which produces waste equivalent to 30% of the original stone in the form of small pieces and powder. Tabas stone is used as an ornament in traditional Balinese buildings, accounting for 50–80% of the construction material in Bali. This waste is often disposed of in rivers, reducing the wet surface area and polluting the environment. On the other hand, mortar as a binding material in construction accounts for about 30% of total building material use, making the use of environmentally friendly local materials in mortar formulations highly relevant. In 2022, out of 1.02 million tons of waste in Bali, about 70% was organic waste. Most of it came from the construction, agriculture, and handicraft sectors, such as bamboo fiber (BF), coconut fiber (CF), and pineapple leaf fiber (PLF). These materials have high cellulose content, namely bamboo powder at 53.6%, coconut husk at 43.44%, and pineapple leaves at 71.5%, which have the potential to be used as environmentally friendly mortar additives. This study aims to evaluate mortar formulations based on basalt scoria with the addition of these fibers from technical, environmental, and cost-efficiency perspectives. The TOPSIS method from the MCDM approach was used to determine the best formulation based on parameter rankings. The results showed that with the addition of 10% cellulose fibers, the compressive strength obtained was 4.137 MPa for bamboo fibers, 3.224 MPa for coconut husk fibers, and 3.923 MPa for pineapple leaf fibers. The ranking results indicate that while bamboo fiber (BF) shows the highest cost efficiency, the MS-12CCF mixture emerges as the most balanced alternative when considering technical, environmental, and economic aspects.